The State of Multilingual Publishing in South Africa - Jana MÖLLER (E-REA)
South Africa’s Constitution (1996) recognises eleven official languages as equal and that all official languages must enjoy parity of esteem and must be treated equitably (Republic of South Africa). This paper investigates the state of multilingual publishing — publishing in all of South Africa’s official languages — and through this how close the country has come to meeting the Constitutional requirements. Findings have shown that most books in South Africa are published in English and Afrikaans and that the nine remaining official languages serve mostly for books to be used in schools. Thus tertiary institution students cannot read books for their studies in their mother tongues, and general readers cannot access books for leisure reading. There are various reasons books are not being published in African languages to any great extent, including historical legacies, few authors and small reading markets.